Effects of anti-factor VIII inhibitor antibodies on factor VIIa/tissue factor-catalysed activation and inactivation of factor VIII - Yada, Koji; Nogami, Keiji; Ogiwara, Kenichi; Shibata, Masaru; Shima, Midori (Thrombosis and Haemostasis, 2011)
Factor (F)VIIa/tissue factor (TF) rapidly activates FVIII activity by proteolysis at Arg372 and Arg740, and subsequently inactivates FVIIIa activity by proteolysis at Arg336, although this activation is weaker than that by thrombin. The effects of anti-FVIII inhibitor antibodies on these reactions remain unknown, however. In this study, 13 of anti-FVIII inhibitor antibodies recognising the A2 or C2 domain were prepared. None of them, irrespective of epitope specificity, significantly affected FVIIa/TFcatalysed FVIII activation in one-stage clotting assays. Anti-A2 and anti-C2 type 2 antibodies had little effect on the inactivation phase. Anti-C2 type 1 antibodies, however, modulated inactivation by 40–60% of that seen with control IgG, suggesting that the activity of FVIIIa generated by FVIIa/TF persisted in the presence of this specific type of inhibitor. SDS-PAGE analysis demonstrated that all antibodies had little effect on FVIIa/TF-catalyzed proteolysis at Arg372 and Arg740. Anti-C2 type 1, however, significantly delayed cleavage at Arg336 in dose-dependent manners. Neither anti-A2 nor anti-C2 type 2 affected this reaction, and the findings were consistent with the results of the functional assays. In addition, anti-C2 monoclonal antibodies with type 1 and 2 demonstrated similar patterns of reaction as the anti-C2 polyclonal antibodies in FVIIa/TF-mediated FVIII mechanisms. We demonstrated that FVIIa/TF activated FVIII even in the presence of anti-FVIII antibodies, but inactivation patterns appeared to depend on inhibitor type. It could be important to determine the characteristic of these inhibitor antibodies for prediction of their effects on FVIIa-related FVIII reactions, and the results could have significant therapeutic implications.Note: An account of this work was presented at the 51st annual meeting of the American Society of Hematology, 2009, New Orleans, LA, USA. This work was supported by grants for MEXT KAKENHI 21591370 in Japan and Bayer Hemophilia Award program.
Keywords: FVIII; FVIII inhibitor antibodies; FVIIa/TF; activation/inactivation; cleavage